Confirming chemical clocks: asteroseismic age dissection of the Milky Way disc(s). Issue 4 (18th January 2018) - Silva Aguirre, V; Bojsen-Hansen, M; Slumstrup, D; Casagrande, L; Kawata, D; Ciucă, I; Handberg, R; Lund, M N; Mosumgaard, J R; Huber, D; Johnson, J A; Pinsonneault, M H; et al.
Abstract: Investigations of the origin and evolution of the Milky Way disc have long relied on chemical and kinematic identifications of its components to reconstruct our Galactic past. Difficulties in determining precise stellar ages have restricted most studies to small samples, normally confined to the solar neighbourhood. Here, we break this impasse with the help of asteroseismic inference and perform a chronology of the evolution of the disc throughout the age of the Galaxy. We chemically dissect the Milky Way disc population using a sample of red giant stars spanning out to 2 kpc in the solar annulus observed by the Kepler satellite, with the added dimension of asteroseismic ages. Our results reveal a clear difference in age between the low- and high-α populations, which also show distinct velocity dispersions in the V and W components. We find no tight correlation between age and metallicity nor [α/Fe] for the high-α disc stars. Our results indicate that this component formed over a period of more than 2 Gyr with a wide range of [M/H] and [α/Fe] independent of time. Our findings show that the kinematic properties of young α-rich stars are consistent with the rest of the high-α population and different from the low-α stars of similar age, rendering support to their origin being old stars that went through a mass transfer or stellar merger event, making them appear younger, instead of migration of truly young stars formed close to the Galactic bar.